2021
DOI: 10.1029/2021gl094772
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Global Ocean Abnormal Mesoscale Eddies Derived From the Fusion of Sea Surface Height and Temperature Data by Deep Learning

Abstract: Mesoscale eddies are broadly distributed in the global ocean and play a significant role in transporting energy, heat, and mass alongside nutrients and chemical elements across ocean basins (Chelton, Gaube,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 58 publications
0
29
1
Order By: Relevance
“…It is worth noting that previous studies usually focus on the cyclonic cold-core eddy (CCE) and anticyclonic warm-core eddy (AWE). In addition to these eddy statistical results (normal eddies, namely, CCE and AWE), recent studies show that there is also an abundance of eddies that do not meet the statistical characteristics (abnormal eddies, that are cyclonic warm-core eddy (CWE) and anticyclonic cold-core eddy (ACE); Itoh and Yasuda, 2010b;Itoh and Yasuda, 2010a;Ji et al, 2016;Sun et al, 2019;Liu et al, 2021;Ni et al, 2021;Sun et al, 2021a). The discovery of these abnormal eddies expands the research content and classification of mesoscale eddies from two types (CCE and AWE) to four (CCE, AWE, CWE, and ACE).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that previous studies usually focus on the cyclonic cold-core eddy (CCE) and anticyclonic warm-core eddy (AWE). In addition to these eddy statistical results (normal eddies, namely, CCE and AWE), recent studies show that there is also an abundance of eddies that do not meet the statistical characteristics (abnormal eddies, that are cyclonic warm-core eddy (CWE) and anticyclonic cold-core eddy (ACE); Itoh and Yasuda, 2010b;Itoh and Yasuda, 2010a;Ji et al, 2016;Sun et al, 2019;Liu et al, 2021;Ni et al, 2021;Sun et al, 2021a). The discovery of these abnormal eddies expands the research content and classification of mesoscale eddies from two types (CCE and AWE) to four (CCE, AWE, CWE, and ACE).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2019) proposed that the abnormal eddy needs to meet the following conditions: 1) the average temperature inside the CWE (ACE) is 0.1°C warmer (colder) than the average temperature of the annular area between the CWE (ACE) boundary and 1.5 times the eddy boundary; 2) the proportion of the warm (cold) temperature points inside the CWE (ACE) is at least 60% of the total points. Liu et al (2021) only used the positive and negative of the filtered temperature anomaly to define the abnormal eddy.…”
Section: Definition Of Four Types Of Eddiesmentioning
confidence: 99%
“…However, with the increasing number of studies focusing on the mesoscale eddy phenomenon, it has been found that there are not only normal eddies, i.e., cyclonic cold-core eddies (CCEs, with anticlockwise flow field and cold eddy core) and anticyclonic warm-core eddies (AWEs, with clockwise rotation flow field and warm eddy core). There are also mesoscale eddies with the opposite properties (Yasuda et al, 2000;Itoh and Yasuda, 2010;Ji et al, 2016;Sun et al, 2019;Sun et al, 2021a;Liu et al, 2021;Ni et al, 2021;Qi et al, 2022): cyclonic warm-core eddies (CWEs, with anticlockwise rotation flow field and warm eddy core), and anticyclonic cold-core eddies (ACEs, with clockwise rotation flow field and cold eddy core).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase of computing power and the development of novel algorithms, deep learning models have become powerful tools that have been widely utilized in hydrology studies (Fang et al, 2017;Orland et al, 2020;Liu et al, 2021;Feng et al, 2021a) in the past few years. The majority of studies focus on daily rainfall-runoff modeling and streamflow forecasting (Kratzert et al, 2018;Kratzert et al, 2019;Feng et al, 2020;Qian et al, 2020;Sarkar et al, 2020;Van et al, 2020;Lees et al, 2021).…”
Section: Introductionmentioning
confidence: 99%